2009
DOI: 10.1100/tsw.2009.142
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and Insulin for Hypertriglyceridemia-Induced Pancreatitis: Case Report

Abstract: Hypertriglyceridemia is the etiology of acute nonbiliary pancreatitis in up to 3% of patients. Along with the supportive treatment of acute pancreatitis, treating the precipitating cause is important as well. There have been reports where heparin and insulin have been used for acute reduction of triglycerides, although there are no established guidelines for efficacy of these modalities. Heparin and insulin decrease triglycerides by stimulating lipoprotein lipase activity, which degrades triglycerides into fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 6 publications
3
35
0
2
Order By: Relevance
“…Serum triglyceride levels in their series decreased to < 500 mg/dL (5.6 mmol/L) within 3 days in all cases. Other authors have also reported successful treatment with heparin and insulin in patients with HTGP (Table 3) (9)(10)(11)(12)(13)(14)(15). No complications from this treatment The dose of heparin for HTGP management has also not been determined by the studies.…”
Section: Heparin and Insulin In Hypertriglyceridemia-associated Pancrmentioning
confidence: 95%
See 1 more Smart Citation
“…Serum triglyceride levels in their series decreased to < 500 mg/dL (5.6 mmol/L) within 3 days in all cases. Other authors have also reported successful treatment with heparin and insulin in patients with HTGP (Table 3) (9)(10)(11)(12)(13)(14)(15). No complications from this treatment The dose of heparin for HTGP management has also not been determined by the studies.…”
Section: Heparin and Insulin In Hypertriglyceridemia-associated Pancrmentioning
confidence: 95%
“…However, more dramatic results have been achieved when both were used in combination (7)(8)(9)(10)(11)(12)(13)(14)(15). Plasma exchange (plasmapheresis) has also been used successfully to treat severe HTGP (22); however, this treatment is far more expensive and may not be available at all health care centers.…”
Section: Heparin and Insulin In Hypertriglyceridemia-associated Pancrmentioning
confidence: 99%
“…The literature search continued with articles referenced on UpToDate® on the "Hypertriglyceridemiainduced acute pancreatitis" webpage regarding the treatment of this condition. Many of the articles concerning the various ISSN: 2379-4550 http://digitalcommons.wayne.edu/crp, © 2018 The Author(s) 2 Licensed under Creative Commons Attribution Non-Commercial 4.0 treatment strategies were case reports [1][2][3][4][5][6] or clinical reviews 7 , and no randomized controlled trials were referenced. The patients managed in these case reports had a wide variety of triglyceride levels (1000 mg/dL to >10000 mg/dL) and lipase levels (300 units/L to >7000 units/L) but most patients showed improvement with several different types of therapy and could be discharged from the hospital with no long-term morbidities.…”
Section: Related Literaturementioning
confidence: 99%
“…In this case, apheresis, insulin and heparin (even combined) are suggested in addition to supportive therapy for pancreatitis early treatment with fibrates. [144][145][146] …”
Section: Hypertriglyceridemiamentioning
confidence: 99%